2011
DOI: 10.1007/s11839-011-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress at work in nurses providing end-of-life palliative care according to care settings

Abstract: Le stress au travail chez les infirmières en soins palliatifs de fin de vie selon le milieu de pratique Stress at work in nurses providing end-of-life palliative care according to care settings L. Fillion · J.-F. Desbiens · M. Truchon · C. Dallaire · G. Roch Reçu le 2 mai 2011 ; accepté le 10 mai 2011 © Springer-Verlag France 2011 Résumé Le stress au travail des infirmières prodiguant des soins palliatifs (SP) de fin de vie dans d'autres milieux que les unités spécialisées de SP demeure peu documenté. Cette é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Several participants working in inpatient settings expressed strong emotions around cases that were traumatic in nature, especially around unexpected or untimely deaths (e.g., young patients). Fillion et al [44] studied nurses working in end-of-life care and other settings in Quebec. Nurses working in critical care and oncology units reported high stress compared with specialized PC units [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several participants working in inpatient settings expressed strong emotions around cases that were traumatic in nature, especially around unexpected or untimely deaths (e.g., young patients). Fillion et al [44] studied nurses working in end-of-life care and other settings in Quebec. Nurses working in critical care and oncology units reported high stress compared with specialized PC units [44].…”
Section: Discussionmentioning
confidence: 99%
“…Fillion et al [44] studied nurses working in end-of-life care and other settings in Quebec. Nurses working in critical care and oncology units reported high stress compared with specialized PC units [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several participants working in inpatient settings expressed strong emotions around cases traumatic in nature, concerning unexpected or untimely deaths (e.g., young patients). Fillion et al [37] studied Quebec nurses working in end of life care. Nurses working in critical care and oncology units reported high stress compared with specialized PC units [37].…”
Section: Discussionmentioning
confidence: 99%
“…Fillion et al [37] studied Quebec nurses working in end of life care. Nurses working in critical care and oncology units reported high stress compared with specialized PC units [37]. Consistent with prior studies, the most common reported responses (50%) were maintaining a need to 'carry on" [16,23] and a stance of not expressing emotion.…”
Section: Discussionmentioning
confidence: 99%
“…The organizational changes involved in implementing an integrated system can be a source of anxiety and negative stressors that affect workplace quality of life. Occupational stressors associated with changing roles and responsibilities, with new requirements to be met, or with role ambiguities have been identified as sources of uncertainty, instability, conflictual relationships, emotional exhaustion, and anxiety [ 17 - 22 ]. Over recent years, as Quebec’s healthcare system has been restructured and services have been integrated, several studies have observed an overall decrease in nurses’ job satisfaction [ 23 - 26 ], a rise in absenteeism, and increased psychological distress [ 21 , 27 - 29 ].…”
Section: Introductionmentioning
confidence: 99%